Eftilagimod alpha, a soluble lymphocyte activation gene-3 (LAG-3) protein plus pembrolizumab in patients with metastatic melanoma. Issue 2 (20th November 2020) - Atkinson, Victoria; Khattak, Adnan; Haydon, Andrew; Eastgate, Melissa; Roy, Amitesh; Prithviraj, Prashanth; Mueller, Christian; Brignone, Chrystelle; Triebel, Frederic
Abstract : Background: To evaluate the safety, tolerability, pharmacokinetics and pharmacodynamics of eftilagimod alpha (efti), a soluble lymphocyte activation gene-3 protein, in combination with the programmed cell death-1 (PD-1) antagonist pembrolizumab. Methods: The study was divided into two parts; parts A and B, where part A was the dose escalation part and part B was an extension part of the study. Patients with metastatic melanoma were treated with efti plus the standard dose of pembrolizumab. Blood samples were assayed to determine plasma pharmacokinetic parameters, detect efti antibody formation and determine long-lived CD8 T cell responses and associated pharmacodynamic parameters. Results: Twenty-four patients with melanoma received pembrolizumab and bi-weekly subcutaneous (s.c.) injections of efti at doses 1 mg, 6 mg or 30 mg/injection for up to 6 months (part A) or 30 mg/injection for up 12 months (part B). No dose-limiting toxicities were reported and the main adverse event for efti was injection site reactions. Sustained systemic exposure to the product was obtained in all patients following s.c. injections of 30 mg dose. Treatment induced an increase in activated CD8 and CD4 T cell counts, and in some of the soluble biomarkers, particularly interferon (IFN)-γ, a Th1 signature cytokine. An overall response rate (ORR) of 33% was observed in patients partly with pembrolizumab-refractory of part A and ORR of 50% was observed in patients with PD-1 naïve of part B. Conclusions: Efti was well tolerated in combination with pembrolizumab with encouraging antitumor activity. This warrants further clinical studies of this new combination therapy combining an antigen-presenting cell activator with an immune checkpoint inhibitor.